The effect of mother's burden on learning from home, maternal-efficacy, and maternal care practices on emotion and negative behavior of children aged 5-6 years - Devi Rahmawati; Dwi Hastuti; Megawati Simanjuntak (Jurnal Cakrawala Pendidikan, 2022)
Mothers play a big role in every aspect of their children’s lives. During learning from home (LfH) period, children's negative behavior can also change and is influenced by maternal-efficacy, maternal burden, and parenting practices. The purpose of this study was to analyze differences in maternal burden and parenting practices before and during LfH and to analyze the effect of mothers' burden on learning from home, maternal-efficacy, and parenting practices on the negative behavior of children aged 5-6 years. This study used a cross-sectional and retrospective study design. This research was conducted in three kindergartens with an A accreditation status in Jagakarsa Village, Jagakarsa District, South Jakarta City, DKI Jakarta Province. The study involved 100 working mothers who were selected using non-probability sampling with a voluntary sampling technique. The results of the influence test showed that the mother's burden during LfH period had a significant negative effect on the mother's maternal efficacy, while the mother's maternal efficacy had a significant positive effect on negative parenting practices and negative child behavior. Based on the research results, the maternal-efficacy of parents was assumed to be not strong enough to prevent negative parenting practices carried out by parents during the Covid-19 pandemic. Furthermore, negative parenting practices by mothers had a significant positive effect on children's negative behavior.